NEW PROOF OF AHLFORS LEMMA ABOUT GREEN STOKES FORMULA FOR DISTRIBUTIONS - Savić, Ana (Bulletin of Natural Sciences Research, 2022)
The paper presents a new proof of Ahlfors lemma about Green Stokes formula for distributions. The proof is performed directly using test functions instead of using convolutions.
Keywords: Convolutions; Distributions; Green Stokes formula; Test functions